Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar Matematika Siswa - Muslimin Muslimin; Yonathan S Passinggi; Nirmalasari Nirmalasari (Universitas Islam Jember, 2023)
The purpose of this study was to find out the description of students' mathematics learning outcomes on the material properties of flat shapes in class III UPT SD Negeri 148 Ketulungan, North Luwu and to determine the effect of using the numbered head together learning model on student mathematics learning outcomes on the material properties of shapes. flat in class III UPT SD Negeri 148 Ketulungan. This type of research is experimental research using the One Group Pretest-Posttest Design and 18 students as samples. The data collection technique uses documentation and tests in the form of multiple choices. While data analysis using descriptive statistical analysis techniques and inferential analysis techniques. Descriptive statistical results were obtained from the results of the students' pretest and posttest tests which were described in the distribution table. Based on the results of inferential statistical analysis by testing the hypothesis using the paired sample t-test showed Sig (2-tailed) <0.005 (0.000 <0.05). So it is obtained that the average score of the pretest learning outcomes is 57.11 and the posttest is 75.50, which means that the numbered head together learning model has an effect on student mathematics learning outcomes on the properties of flat shapes in class III UPT SD Negeri 148 Ketulungan, Luwu Utara . Keywords: number head together, mathematics learning outcomes